2007
DOI: 10.1590/s1413-70542007000200038
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de lisina para suínos machos castrados selecionados geneticamente para deposição de carne magra na carcaça, dos 95 aos 122 kg

Abstract: RESUMOUm experimento foi realizado para se determinar as exigências de lisina de suínos machos castrados, na fase de terminação tardia, avaliando-se os efeitos de diferentes níveis de lisina da ração sobre o desempenho e características de carcaça dos animais. Utilizaram-se 50 suínos híbridos comerciais (AG-PIC 412 X C-22), com peso inicial de 95,39 ± 0,85 kg e final de 122,29 ± 3,02 kg, distribuídos em delineamento experimental de blocos ao acaso, com cinco tratamentos (0,5; 0,6; 0,7; 0,8 e 0,9 % de lisina to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
3
5
1
1
Order By: Relevance
“…Feed intake was not affected (P>0.05) by the digestible lysine levels, which is consistent with the results obtained by Friesen et al (1995), Cline et al (2000), Arouca et al (2005), Abreu et al (2007), Arouca et al (2007) and Marino et al (2007b). Other authors (Gonçalves et al, 1999;Oliveira et al 2003) have however observed reductions in feed intake with increasing levels of dietary lysine.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Feed intake was not affected (P>0.05) by the digestible lysine levels, which is consistent with the results obtained by Friesen et al (1995), Cline et al (2000), Arouca et al (2005), Abreu et al (2007), Arouca et al (2007) and Marino et al (2007b). Other authors (Gonçalves et al, 1999;Oliveira et al 2003) have however observed reductions in feed intake with increasing levels of dietary lysine.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, Marinho et al (2007a) found no effect of digestible lysine levels (0.67 and 0.87%) in diets with or without ractopamine (5.0 ppm) on pigs' performance. Arouca et al (2007) assessed the levels of digestible lysine (0.50-to 0.90%) for 95-to 122-kg pigs and found a lysine requirement of 0.71%. Kiefer & Sanchez (2009) verified that pigs' weight gain linearly increased as dietary lysine increased in all levels of ractopamine, including the diet with no ractopamine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary aP concentrations that maximized ADG were 0.200, 0.307, and 0.350% in the experiments reported by Ketaren et al (1993), Stahly et al (2000), and Arouca (2008). These differences may have been caused by differences in the genetic potential for lean gain among pigs used in the different experiments because data reported by Hendriks and Moughan (1993) and Mahan (2006) indicated that pigs with different lean growth potentials may have different mineral requirements.…”
Section: Discussionmentioning
confidence: 86%
“…Por sua vez, Arouca et al (2007) (Kill et al, 2003) e machos não castrados (Kiefer et al, 2012). Main et al (2008) também registraram melhora no desempenho de machos castrados e fêmeas de 35 a 120 kg em função do aumento da concentração de lisina.…”
Section: Resultsunclassified